Investigating the Effectiveness of Schema Therapy on Intolerance of Uncertainty, Rejection Sensitivity, and Self-Critical Rumination in Women Victims of Emotional Abuse - Safdari Ghooshchi, Zivar (Applied Family Therapy Journal (AFTJ), 2026)
Objective: The present study aimed to investigate the effectiveness of schema therapy on intolerance of uncertainty, rejection sensitivity, and self-critical rumination among women victims of emotional abuse.Methods and Materials: In terms of purpose, this study was applied research, and in terms of design, it was a quasi-experimental study employing a pretest–posttest design with follow-up and a control group. The statistical population consisted of all women victims of emotional abuse who referred to counseling centers, psychological clinics, and support centers for victims of unhealthy relationships in Tehran in 2025. The research sample was selected using purposive and convenience sampling methods and included 30 women who, after meeting the inclusion criteria and completing informed consent forms, were randomly assigned to an experimental group (n = 15) and a control group (n = 15). The experimental group received schema therapy intervention during 10 weekly 60-minute sessions, whereas the control group received no intervention during this period. Data were collected using the Intolerance of Uncertainty Questionnaire (Carleton et al., 2007), the Rejection Sensitivity Scale (Downey & Feldman, 1996), and the Self-Critical Rumination Questionnaire (Smart et al., 2016). The instruments demonstrated adequate validity and reliability in both Iranian and international samples. Data were collected at three stages, including pretest, posttest, and follow-up, and were analyzed using repeated-measures analysis of variance in IBM SPSS Statistics.Findings: The findings indicated that schema therapy significantly reduced intolerance of uncertainty, rejection sensitivity, and self-critical rumination in the experimental group compared with the control group (p < .001), and these improvements remained stable at the follow-up stage. Furthermore, the large effect sizes and complete statistical power indicated the strong and robust effectiveness of the intervention.Conclusion: Based on the findings, it can be concluded that schema therapy is an effective approach for reducing the cognitive-emotional vulnerabilities of women victims of emotional abuse and may be implemented as an empowering psychological intervention in counseling and support service centers.